Traveling-wave transcranial alternating current stimulation (twtACS) causally links neural timing to cognitive function - Sangjun Lee; Jimin Park; Ivan Alekseichuk; Taylor A. Berger; Ana M. G. Manea; Harry Tran; Gabriela Delgado Salazar; Seth D. König; Alexander B. Herman; David P. Darrow; Jan Zimmermann; Alexander Opitz (Proceedings of the National Academy of Sciences, 2026)
Cortical traveling waves (TWs) are brain oscillation patterns that support the transfer of neural information across distinct brain regions, with their direction shaping cognitive function. However, direct evidence for their causal influence on brain dynamics and behavior remains lacking. Here, we establish such a causal link by externally applying TW-like electric field patterns. To achieve this, we develop a noninvasive brain stimulation protocol, traveling-wave transcranial alternating current stimulation (twtACS). twtACS can generate a precise directional electric field that propagates across the cortical surface, which we validate using human intracranial recordings. In monkey recordings, we show that neural spiking was directionally modulated, shifting systematically across space in line with the direction of twtACS. In humans, twtACS led to direction-dependent improvements in cognitive performance. Together, these findings demonstrate that externally imposed TWs can causally shape neural activity and cognition, highlighting the potential of twtACS as a neuromodulation technique for cognitive enhancement.